Potential Effects of Neem Plants (Azadirachta indica A. Juss.) as Antidiabetic - Putri Rachma Novitasari; Baiq Maylinda Gemantari; Syarifatul Mufidah; Prita Anggraini Kartika Sari (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2021)
Many people choose alternative medicines for Diabetes Mellitus (DM) disorders, such as herbal plants to suppress the occurrence of the disease widely. In general, DM occurs when the pancreas doesn't produce enough insulin, or when the body can't effectively use the insulin which it produces. The use of medicinal plants to treat various diseases has shown minimal side effects. Indonesia is one of the countries that has used plants as traditional medicine since ancient times. In Indonesia, thousands of species of medicinal plants have been studied to address health problems. Among the medicinal plants that have been studied is the Neem plant (Azadirachta indica A. Juss) which has been shown to cure various diseases. This review article describes the potential of the Neem plant as an antidiabetic. The results of this literature review, in the form of Neem herbal extracts, have quite good potential as an antidiabetic because they contain several compounds such as meliacinolin, azachdirichtin, gliserid oil, acetyl oxyturanoe acid and other compounds that can also act as antidiabetic.